Basic English conversation training for tourism actors on Untung Jawa Island - Yanti Yanti; Christine Manara (Community Empowerment, 2022)
During the Covid-19 pandemic, tourism activities almost stopped. Tourism actors on the Untung Jawa island attempt to improve tourism facilities and infrastructure and increase the capacity of their human resources. The purpose of this activity is to improve communication skills in English. The results of the pre-training questionnaire show that the required English is conversational English at the basic level. The method of community service activities is online basic level conversational English training using drill techniques. The materials are arranged according to language functions and the participants are divided into small groups of four to six people. The results of the activity showed that the participants were able to initiate and engage in short conversations using phrases and making short narratives.